ANALISIS KINERJA PEMUNGUTAN DAN RETRIBUSI PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA BATAM - Syahril Effendi; Neni Marlina Br Purba (JURNAL AKUNTANSI BARELANG, 2019)
This study aims to find answers to the performance level of billboard tax collection in Batam City, and its contribution to local tax revenues in Batam City. This research applies descriptive analysis method, where this method is used to provide systematic explanations, actual and accurate statements of facts, and only describe situations or events not to find or explain relationships and test hypotheses. The object of this research is the Batam City Dispenda. The sampling technique used is non probability sampling, namely the technique of determining the sample using certain considerations or in (purposive sampling) using financial statements from 2011 to 2015. The results of the hypothesis test show that simultaneous performance of collection and levy on advertisement tax collection in the Dispenda Batam City has a significant effect on local revenue. While partially the collection performance at the Batam City Dispenda has a significant relationship to local original income, however, advertisement tax collection levies have a significant influence on local revenue in Batam City Dispenda